Characterization and Comparison of the Rumen Luminal and Epithelial Microbiome Profiles Using Metagenomic Sequencing Technique - Stockler, Ricardo M.; Hallowell, Haley; Higgins, Keah V.; Groover, Erin S.; Hiltbold, Elizabeth M.; Newcomer, Benjamin; Walz, Paul H. (Frontiers in Veterinary Science, 2022)
Bacterial dysbiosis as a result of nutritional, bacterial, viral, and parasitic gastrointestinal infections can adversely affect the metabolism, productivity, and overall health of cattle. The purpose of this project was to characterize the commensal microbiota present in two locations of the rumen concomitantly in vivo with the animals undergoing habitual husbandry, as it was hypothesized that there are major differences in the commensal microbiota present in the two locations of the adult bovine major forestomach. A surgically fitted rumen cannula was used to allow ruminal lumen contents and mucosal biopsies to be collected from six crossbred yearling steers. In order to assess as much environmental and individual steer microbiota variation as possible, each animal was randomly sampled three times over a three week period. 16S rRNA sequencing was performed to provide a detailed descriptive analysis from phylum to genus taxonomic level. Significant differences were observed between luminal and epimural bacterial populations in the bovine rumen. As expected, a core microbiome composed by Firmicutes and Bacteroidetes represented over 90% of the microbiome, however, further analysis showed distinct diversity and distribution of the microbiome between the two locations. Characterizing the gastrointestinal microbiome in vivo is imperative. The novelty and the contribution of this study to the literature is the use of live cattle which allowed real-time sample collections and analysis of the rumen microbiome providing an understanding of what is normal in the live animal.